An acceptance model of mobile banking - Sathitwiriyawong, Chanboon; Phuttaraksa, Pornnapa (My University, 2018)
This paper examines the influence of five external variables regarding the acceptance of mobile banking based on technology acceptance model (TAM) and trust model. They are system quality, self-efficacy, subjective norm, structural assurance, and compatibility. The population samples are retail bank customers residing in Bangkok who have experience in mobile banking services. Structural equation modeling is used to evaluate the causal relationship in the proposed model. The results of path coefficient analysis indicate that the acceptance of mobile banking is mainly influenced by behavioral intention to use. The acceptance of mobile banking can be explained by behavioral intention to use by 40 percent. Furthermore, compatibility emerged as the most powerful factor influencing the behavioral intention to use compared with the other factors.
Keywords: mobile banking; structural equation modeling; TAM; technology acceptance model; trust model